KONSEP MENDIDIK ANAK CINTA AL-QUR’AN SEJAK DINI (KAJIAN SURAH AL-A’RAAF AYAT 204-206) - Laza, Isna Naila; Hamzah, Muchotob; Mukromin, Mukromin (AL-QALAM: JURNAL KEPENDIDIKAN, 2022)
In this digital era where increasingly sophisticated technological developments. Children are more fond of applying internet work, then that is where the role of educators is needed to direct children to positive activities. One of them is by teaching the Al-Qur’an education. The purpose of writing to know concept educating children love al-qur’an from an early age with Q.S Al-A’raaf verse 204-206. This research is a qualitative research using the library method, which is a study that uses some literature as the object of research. Data collection techniques are form documentation, discourse from several references. While data analysis uses the tahlily and the maudhu’i method. Research results show : 1. The obligation of educators (parents, teachers, community) to provide education to children to help the prosess of child development more optimally. 2. In general, the mufassir’s interpretation of Q.S Al-A’raaf verses 204-206 must listen and pay attention when the Qur’an is read and always rememberance of Allah is done with humility, sincerity and a soft voice. 3. The importance of teaching children to instill a sense of love for the qur’an in early childhood because interacting with the qur’an is a tangiable manifestation as an appreciation of human love for Allah.